2002
DOI: 10.1071/ah020107
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and characteristics of ethnic Australian women utilising ethno-specific maternal and child health services

Abstract: Few studies have explored the socio-economic profile, service utilisation, obstetric history and pregnancy outcomes of ethnic women who utilise ethno-specific obstetric services in Australia. The purpose of this study was to form a profile of women who accessed the Ethnic Obstetric Liaison Services (EOLO) in South Western Sydney Area Health Service (SWSAHS), New South Wales and explore their beliefs about using maternal and infant health services. We found that the prevalence of risks and special needs varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…All of the studies were conducted in high-income countries. The countries with the highest numbers of studies were Canada, 15 studies (Ballantyne et al 2013 ; Dennis et al 2004 ; Gagnon et al 2013 ; Ganann et al 2012 ; Lanes et al 2011 ; McDonald et al 2013 ; Mechakra-Tahiri et al 2007 ; Minde et al 2001 ; Miszkurka et al 2010 ; Peer et al 2013 ; Stewart et al 2008 , 2012 ; Sword et al 2006 ; Van Lieshout et al 2011 ; Zelkowitz et al 2008 ); the USA, 14 studies (Balbierz et al 2014 ; Connelly et al 2013 ; Davila et al 2009 ; Diaz et al 2007 ; Elo and Culhane 2010 ; Fleuriet and Sunil 2014 ; Fortner et al 2011 ; Goyal et al 2006 ; Harrison and Sidebottom 2009 ; Heilemann et al 2004 ; Huang et al 2007 ; Luecken et al 2013 ; Valentine et al 2011 ; Yeung and Schwartz 1986 ); Australia, 7 studies (Bandyopadhyay et al 2010 ; Eastwood et al 2011 ; Milgrom et al 2008 ; Shafiei et al 2015 ; Small et al 2003 ; Tran et al 2002 ; Yelland et al 2010 ); and Taiwan, China, 6 studies (Chen et al 2013 ; Chen et al 2012 ; Chien et al 2012 ; Huang and Mathers 2008 ; Hung et al 2012 ; Tsao et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the studies were conducted in high-income countries. The countries with the highest numbers of studies were Canada, 15 studies (Ballantyne et al 2013 ; Dennis et al 2004 ; Gagnon et al 2013 ; Ganann et al 2012 ; Lanes et al 2011 ; McDonald et al 2013 ; Mechakra-Tahiri et al 2007 ; Minde et al 2001 ; Miszkurka et al 2010 ; Peer et al 2013 ; Stewart et al 2008 , 2012 ; Sword et al 2006 ; Van Lieshout et al 2011 ; Zelkowitz et al 2008 ); the USA, 14 studies (Balbierz et al 2014 ; Connelly et al 2013 ; Davila et al 2009 ; Diaz et al 2007 ; Elo and Culhane 2010 ; Fleuriet and Sunil 2014 ; Fortner et al 2011 ; Goyal et al 2006 ; Harrison and Sidebottom 2009 ; Heilemann et al 2004 ; Huang et al 2007 ; Luecken et al 2013 ; Valentine et al 2011 ; Yeung and Schwartz 1986 ); Australia, 7 studies (Bandyopadhyay et al 2010 ; Eastwood et al 2011 ; Milgrom et al 2008 ; Shafiei et al 2015 ; Small et al 2003 ; Tran et al 2002 ; Yelland et al 2010 ); and Taiwan, China, 6 studies (Chen et al 2013 ; Chen et al 2012 ; Chien et al 2012 ; Huang and Mathers 2008 ; Hung et al 2012 ; Tsao et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies were cross-sectional surveys (Abbott and Williams 2006 ; Balestrieri et al 2012 ; Ballantyne et al 2013 ; Chen et al 2012 ; Chien et al 2012 ; Choi et al 2012 ; Davila et al 2009 ; Dennis et al 2004 ; Eastwood et al 2011 ; Elo and Culhane 2010 ; Fisch et al 1997 ; Fleuriet and Sunil 2014 ; Ganann et al 2012 ; Glasser et al 2000 ; Goyal et al 2006 ; Harrison and Sidebottom 2009 ; Heilemann et al 2004 ; Huang and Mathers 2008 ; Hung et al 2012 ; Lanes et al 2011 ; Mechakra-Tahiri et al 2007 ; Minde et al 2001 ; Miszkurka et al 2010 ; Peer et al 2013 ; Ratcliff et al 2015 ; Shafiei et al 2015 ; Small et al 2003 ; Stewart et al 2008 ; Sword et al 2006 ; Yelland et al 2010 ; Yeung and Schwartz 1986 ), 20 were prospective cohorts (Bandyopadhyay et al 2010 ; Bjerke et al 2008 ; Chen et al 2013 ; Diaz et al 2007 ; Escribà-Agüir et al 2013 ; Fortner et al 2011 ; Gagnon et al 2013 ; Huang et al 2007 ; Jayaweera and Quigley 2010 ; Luecken et al 2013 ; McDonald et al 2013 ; Milgrom et al 2008 ; Rudman et al 2008 ; Stewart et al 2012 ; Tran et al 2002 ; Tsao et al 2014 ; Valentine et al 2011 ; Van Lieshout et al 2011 ; Yoshida et al 1997 ; Zelkowitz et al 2008 ) and two were randomized controlled trials (Balbierz et al 2014 ; Connelly et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tran et al [91] profiled 829 clients of the Ethnic Obstetric Liaison Officer Service in the south west of Sydney and concluded that ethnic-specific service models are necessary for linguistic and cultural relevance; Heaney and Moreham [92] surveyed 109 hospital staff and found they reported under-usage of professional interpreters and inappropriate usage of family and friends as interpreters; Chan and Quine [93] conducted focus groups in Chinese to determine the health needs of this community; Han [94] explored the factors sustaining usage of herbal medicines by Koreans in Australia; Renzaho [89] negatively reviewed community service delivery to culturally and linguistically diverse populations and suggested a new model of needs-led 'cultural consultation' be implemented; Murray and Skull [88], discussed the barriers to care faced by refugees, including language, culture, legal, employment and policy barriers, and outlined available health and social resources and entitlements; Wen et al [90] found culturally diverse populations were less likely to be visited by child health nurses or volunteers and more likely to find such visits 'uncomfortable'; and Strong et al examined the health status of overseas born Australians and found lower reported mortality and hospital utilisation [95]. …”
Section: Resultsmentioning
confidence: 99%